Inverkan av ensilagets partikelstorlek på beteende och beteendestörningar hos mjölkraskvigor - Lidback, Felicia (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
Modern milk production have come a long way when it comes to accommodating the nutritional and physiological needs of the animals, but unfortunately the behavioural and psychological needs of cows and heifers are often left unfulfilled. A long time for eating is beneficial for the digestion and also gives the cattle something to do and decreases the risks for developing abnormal behaviours. An important factor that influences eating- and ruminating time is the particle size of the roughage. The aim of the study was to find out if particle size influences the behaviour of dairy heifers, in particular with regard to eating behaviour and abnormal behaviours.